Comparative study of children and adolescents referred for eating disorder treatment at a specialist tertiary setting. Issue 1 (28th October 2013) - Walker, Tara; Watson, Hunna J.; Leach, David J.; McCormack, Julie; Tobias, Karin; Hamilton, Matthew J.; Forbes, David A.
ABSTRACT Objective To examine child and adolescent differences in the clinical presentation of eating disorders (EDs) at referral to a specialist pediatric program. Method This study compared cognitive, behavioral, and physical and medical features of children (≤12 years) and adolescents (13–18 years) with EDs presenting to a state‐wide specialist pediatric ED service over two decades (N = 656; 8–18 years; 94% female). Results Significant differences were found between the groups. Children were more commonly male (p < .001), had lower eating pathology scores (p < .001), were less likely to binge eat (p = .02), purge (p < .001) or exercise for shape and weight control (p < .001), and lost weight at a faster rate than adolescents (p = .009), whereas adolescents were more likely to present with bulimia nervosa spectrum disorders (p = .004). Children and adolescents did not differ significantly on mean body mass index z‐score, percentage of body weight lost, or indicators of medical compromise (p > .05). Discussion The clinical presentation of EDs differs among children and adolescents, with eating pathology and behavioral symptoms less prominent among children. Frontline health professionals require knowledge of these differences to assist with early detection, diagnosis, and prognosis. © 2013 Wiley Periodicals, Inc. (Int J Eat Disord 2014; 47:47–53)